2010
DOI: 10.1021/nn100213v
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mapping of Tumor Heterogeneity on Clinical Tissue Specimens with Multiplexed Quantum Dots

Abstract: Tumor heterogeneity is one of the most important and challenging problems not only in studying the mechanisms of cancer development but also in developing therapeutics to eradicate cancer cells. Here we report the use of multiplexed quantum dots (QDs) and wavelength-resolved spectral imaging for molecular mapping of tumor heterogeneity on human prostate cancer tissue specimens. By using a panel of just four protein biomarkers (E-cadherin, high-molecular-weight cytokeratin, p63, and α-methylacyl CoA racemase), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
118
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(119 citation statements)
references
References 39 publications
0
118
0
1
Order By: Relevance
“…14B). 245 As in the previous study, the biomarkers were detected using four different colors of QD-secondary antibody conjugate (QD 565 , QD 605 , QD 655 , QD 705 ), revealing molecular and morphological details that are unseen with traditional staining methods. One of the most important observations was that progressive changes in benign prostate glands start with a single malignant cell and ultimately lead to a malignant gland.…”
Section: Bioanalysis and Bioimaging With Quantum Dotsmentioning
confidence: 91%
See 1 more Smart Citation
“…14B). 245 As in the previous study, the biomarkers were detected using four different colors of QD-secondary antibody conjugate (QD 565 , QD 605 , QD 655 , QD 705 ), revealing molecular and morphological details that are unseen with traditional staining methods. One of the most important observations was that progressive changes in benign prostate glands start with a single malignant cell and ultimately lead to a malignant gland.…”
Section: Bioanalysis and Bioimaging With Quantum Dotsmentioning
confidence: 91%
“…In contrast, Nie's group has used multispectral imaging with multiple colors of QD to reliably detect and characterize tumor cells in c o m p l e x t i s s u e m i c r o e n v i r o nments. 244,245 In one study, four protein biomarkers-CD15, CD30, CD45, and Pax5-were simultaneously mapped in lymph node biopsy specimens by using four colors of QD-secondary antibody conjugates (QD 525 , QD 565 , QD 605 , and QD 655 ) as shown in Fig. 14A.…”
Section: Bioanalysis and Bioimaging With Quantum Dotsmentioning
confidence: 99%
“…29 Liu et al have revealed extensive tumor heterogeneity at the molecular, cellular, and architectural levels by the multiplexed QDs and wavelength-resolved spectral imaging for molecular mapping of tumor heterogeneity on human prostate cancer tissue specimens. 30 Multiplexed detection of biomarker in lung cancer, triple-negative breast cancer and head and neck cancer is possible. [31][32][33] Herein, the unique optical and electronic properties of QDs have been fully displayed.…”
mentioning
confidence: 99%
“…Genetic heterogeneity mapping approaches in pancreatic cancer have relied either on generation of a single cell suspension 3 , or on macrodissection 4 . A recent study has used quantum dots in order to map morphologic and molecular heterogeneity in prostate cancer tissue 5 , providing proof of principle that morphology and molecular mapping is feasible, but falling short of quantifying the heterogeneity. Since immunohistochemistry is, at best, only semi-quantitative and subject to intra-and inter-observer bias, more sensitive and quantitative methodologies are required in order to accurately map and quantify tissue heterogeneity in situ.…”
mentioning
confidence: 99%